Dual lumen balloon catheter – An effective substitute for two single lumen catheters in treatment of vascular targets with challenging anatomy. (May 2018) - Borota, Ljubisa; Mahmoud, Ehab; Nyberg, Christoffer; Lewén, Anders; Enblad, Per; Ronne-Engström, Elisabeth
Highlights: Clinical significance of use of dual lumen balloon catheters. Treatment of wide range of pathological vascular conditions of the brain and spine. Safe use of those devices even in blood vessels with very small diameter. Safe treatment of vascular target with challenging anatomy. Differences between dual lumen balloon catheters and single lumen balloons and catheters. Abstract: The aim of this study was to describe our experience in the treatment of various pathological conditions of the cranial and spinal blood vessels and hypervascularized lesions using dual lumen balloon catheters. Twenty-five patients were treated with endovascular techniques: two with vasospasm of cerebral blood vessels caused by subarachnoid hemorrhage, one with a hypervascularized metastasis in the vertebral body, two with spinal dural fistula, four with cerebral dural fistula, three with cerebral arteriovenous malformations, and 13 with aneurysms. The dual lumen balloon catheters were used for remodeling of the coil mesh, injection of various liquid embolic agents, particles and nimodipine, for the prevention of reflux and deployment of coils and stents. The diameter of catheterized blood vessels varied from 0.7 mm to 4 mm. Two complications occurred: perforation of an aneurysm in one case and gluing of the tip of balloon catheter by embolic material in another case. All other interventions were uneventful, and therapeutic goals were achieved in all cases except in the case with gluing of the tip of balloon catheter. The balloons effectively prevented reflux regardless of the type of the embolic material and diameter of blood vessel. The results of our study show that dual lumen balloon catheters allow complex interventions in the narrow cerebral and spinal blood vessels where the safe use of two single lumen catheters is either limited or impossible.